Advancements in eco-friendly lead-free perovskite/Sb2Se3 tandem solar cells: TCAD simulations - Tarek I. Alanazi; Ahmed Shaker; Dalia Selim; Mohamed Okil (Ain Shams Engineering Journal)
In light of the urgent need for sustainable energy solutions, this research addresses the critical environmental concerns of traditional lead-based perovskite materials. This paper explores advancements in an eco-friendly tandem solar cell (TSC) that incorporates both lead-free wide bandgap perovskite and narrow bandgap antimony selenide (Sb2Se3), focusing on optimization strategies utilizing TCAD numerical simulations. The study begins with the calibration of experimental standalone solar cells based on wide bandgap lead-free perovskite (1.62 eV) with a p-i-n heterostructure and narrow bandgap Sb2Se3 (1.2 eV) with an n-i-p configuration. The research then transitions to evaluating the lead-free perovskite/Sb2Se3 system in a four-terminal (4-T) tandem, followed by optimization of the top cell to an n-i-p heterostructure for compatibility with a two-terminal (2-T) structure. Key optimization areas include replacing the organic hole transport layer (HTL) with other inorganic candidates, conduction band offsets (CBOs), and absorber thicknesses. Through these optimizations, the 2-T tandem design achieves a significant improvement, with a simulated PCE reaching 30.96 %. Numerical simulations using TCAD tools are employed to predict performance and guide experimental modifications. This research integrates material science and advanced TCAD simulations to optimize TSC performance with a focus on eco-friendly materials for environmental sustainability.